Health Impacts of Air Pollution from Forest Fires: A Bibliometric Study of Respiratory Diseases - Elisa Suryani; Elsa Yuniarti (Jurnal Biologi Tropis, 2026)
Wildfires are a major source of air pollutants, particularly PM2.5, that pose serious risks to respiratory health. This study aimed to map research trends and thematic developments related to wildfire-related air pollution and respiratory diseases using a bibliometric approach. A total of 188 Scopus-indexed articles published between 2015 and 2025 were analyzed using VOSviewer to examine co-authorship networks, keyword co-occurrence, and citation patterns. The results show a steady increase in publications over the past decade, with dominant research themes focusing on PM2.5 exposure and respiratory outcomes such as asthma and chronic obstructive pulmonary disease. However, existing studies are largely concentrated in high-income countries, with limited attention to long-term health effects and developing regions. These findings highlight critical research gaps and provide a scientific basis for strengthening future research directions and public health policies to mitigate respiratory risks associated with wildfire smoke.